Highly effective treatment of skull base chordoma with carbon ion irradiation using a raster scan technique in 155 patients: First long‐term results. Issue 21 (19th June 2014) - Uhl, Matthias; Mattke, Matthias; Welzel, Thomas; Roeder, Falk; Oelmann, Jan; Habl, Gregor; Jensen, Alexandra; Ellerbrock, Malte; Jäkel, Oliver; Haberer, Thomas; Herfarth, Klaus; Debus, Jürgen
<x xml:space="preserve">Abstract</x> BACKGROUND The current study was conducted to evaluate the long‐term results of irradiation with carbon ions in a raster scanning technique in patients with skull base chordomas. METHODS Between 1998 and 2008, a total of 155 patients (76 men and 79 women) with a median age of 48 years (range, 15 years‐85 years) were irradiated with carbon ions using a raster scan technique. The irradiation was performed at the Society for Heavy Ion Research in Darmstadt, Germany. The median total dose was 60 gray (relative biological effectiveness) at 3 gray (relative biological effectiveness) per fraction. The median boost planning target volume was 70 mL (range, 2 mL‐294 mL). Local control (LC) and overall survival (OS) were evaluated using the Kaplan‐Meier method, whereas long‐term toxicity was evaluated via questionnaires. RESULTS The median follow‐up was 72 months (range, 12 months‐165 months). All patients had residual macroscopic tumors at the initiation of radiotherapy. The authors observed 55 local recurrences during follow‐up, as well as systemic disease progression in 4 patients. The resulting 3‐year, 5‐year, and 10‐year LC rates were 82%, 72%, and 54%, respectively, whereas the 3‐year, 5‐year, and 10‐year OS rates were 95%, 85%, and 75%, respectively. Age <48 years and a boost volume >75 mL were associated with a significantly improved LC and OS. Primary treatment resulted in a significantly better OS probability. No higher late toxicity could be detected after carbon ion treatment. CONCLUSIONS Carbon ion therapy appears to be a safe and effective treatment for patients with skull base chordoma, resulting in high LC and OS rates. Cancer 2014;120:3410–3417. © 2014 American Cancer Society.